The influence of computer self-efficacy, internet self-efficacy and contextual elements on technopreneurial intention: individual entrepreneurial orientation (IEO) as mediator / Mohd Rusydi Abdul Rahim - Abdul Rahim, Mohd Rusydi (2022)
Malaysia recorded low scores in a few entrepreneurial behaviors and attitudes identified by Global Entrepreneurial Monitor (GEM). Besides, not many Malaysians have established new businesses and the early stage entrepreneurship rate is still low and even decreasing. In addition, university students are showing low interest to become entrepreneurs during their tertiary education. Thus, studies regarding technology-based entrepreneurship development in Malaysia is indeed needed. The aim of this study is to investigate the influence of computer self-efficacy, internet self-efficacy and contextual elements (access to capital, access to information and social network) on technopreneurial intention among Bumiputera university (UiTM) students and to examine the mediation effects of individual entrepreneurial orientation (IEO) on the relationship between information communication technology (ICT) self-efficacy (i.e: computer self-efficacy and internet self-efficacy), contextual elements and technopreneurial intention. In this study, the focus area is main branch which UiTM Shah Alam and core branch which is Puncak Alam and Puncak Perdana. As Academic Affair Unit (HEA) in UiTM has provide the relevant student name lists according to campus and branch, this study was conducted probability sampling. Under probability sampling, a proportionate stratified random sampling was be used, where member in the sample from each subgroup will be proportionate to the total number of the elements in the representative strata. The number of population acquired from Academic Affair Unit (HEA) in UiTM is 5030. Based on Krejcie and Morgan table (1970), the minimum sample were be needed is 357. However, this study decided to round up to 360 as minimum sample. 360 final year students (UiTM) in various program and faculties was be selected randomly to be the respondents to answer the questionnaire. IBM SPSS was used as data entry and analysis the data such as preliminary analysis, respondent demographic profile, reliability analysis, descriptive analysis, correlation and last not least is regression (Multi-Collinerity). SEM (AMOS software) analysis technique was be used to analyses the data specifically for the mediator in this study. The result shows the contextual element positively influence the technopreneurial intention and individual entrepreneurial orientation (IEO) mediate the relationship between contextual elements and technopreneurial intention. Thus, this finding result is important as the contextual element has a few aspect which is access to capital, access to information and social network. This results can be used to establish effective ways to solve the problem low early stage in entrepreneurship. In terms of the major contributions of this research, it created a new model for exploring technopreneurial intention and helps government find external factor that influence student intention.